2020
DOI: 10.1242/bio.054627
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine triphosphate Binding Cassette subfamily C member 1 (ABCC1) overexpression reduces APP processing and increases alpha- versus beta-secretase activity, in vitro

Abstract: The organic anion transporter Adenosine triphosphate Binding Cassette subfamily C member 1 (ABCC1), also known as MRP1, has been demonstrated in murine models of Alzheimer's disease (AD) to export amyloid beta (Abeta) from the endothelial cells of the blood-brain barrier to the periphery, and that pharmaceutical activation of ABCC1 can reduce amyloid plaque deposition in the brain. Here, we show that ABCC1 is not only capable of exporting Abeta from the cytoplasm of human cells, but also that it's overexpressi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…A single significant SNP (2L_12758562_SNP) was not annotated to any particular gene in our analysis, but falls within a noncoding region of Multidrug-Resistance like Protein 1 ( MRP ), whose mammalian ortholog is a transporter that has been shown to export Aβ from the endothelium of the blood brain barrier ( Krohn et al . 2011 ; Jepsen et al . 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…A single significant SNP (2L_12758562_SNP) was not annotated to any particular gene in our analysis, but falls within a noncoding region of Multidrug-Resistance like Protein 1 ( MRP ), whose mammalian ortholog is a transporter that has been shown to export Aβ from the endothelium of the blood brain barrier ( Krohn et al . 2011 ; Jepsen et al . 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…For dataset 3, since original study 26 did not distinguish between AD1 and AD2, we could not compare their results with ours. For datasets 4 and 5, since original studies 12,27 compared treated cell lines with controls, which we did not try, we could not compare their results with ours. For dataset 6, since original studies 28 did not compare AD samples and controls directly, but in only tissue specific manner, we could not compare their results with ours.…”
Section: Comparisons With the Original Individual Studiesmentioning
confidence: 89%
“…This activity is reduced in the AD brain ( Lovell et al, 1998 ; Abuznait and Kaddoumi, 2012 ). A recent report suggested that in addition to its exporting of Aβ, ABCC1 may also lower Aβ levels by increasing the ratio of α- to β-secretase cleavage of APP ( Jepsen et al, 2021 ).…”
Section: Abc Transporters Involved In Clearance Of Cerebral Aβmentioning
confidence: 99%